Avaliação de suportes para a imobilização de Zymomonas mobilis CCT 4494 visando à produção de etanol e levana - Santos, Vidiany Aparecida Queiroz [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Zymomonas mobilis is considered to have high biotechnological potential for ethanol and levan production, because it produces little biomass and shows good tolerance to ethanol concentrations. However, this efficiency can be decreased if the free cells are exposed to unfavorable conditions during conventional fermentations. Cell immobilization is an alternative to solve this problem and offers numerous advantages such as higher cell concentrations, greater stability and improved production. Thus the aim of this work was to select a suitable support for the immobilization of Zymomonas mobilis in order to increase the production of ethanol and levan from sucrose as the carbon source. The optimum values for ethanol and levan production were determined using response surface methodology (RSM). The first experiment was a 2(5-2) design with the following independent variables: sucrose concentration, pH, incubation time, temperature and agitation of the culture medium. Based on the best conditions observed in the 2(5-2) experiment, reuse of the support was evaluated during 12 days of fermentation. Ethanol production was determined by microdiffusion and the levan production on fructose units after acid hydrolysis. The biomass was determined by optical density at 570 nm and microbial growth on the support was verified by scanning electron microscopy. In the 2(5-2) experiment the loofa sponge was the best support for immobilization with the highest values for immobilized biomass (2.95 g/L); levan production (24.9 g/L) and ethanol production (50.95 g/L). In the immobilization support reuse experiments in batch fermentations, all the supports evaluated could be reused for 12 cycles, with the exception of chitosan beads. Sugarcane bagasse was shown to be the best substrate for microbial adhesion (3.23 g/L) and for levan (32.13 g/L) and ethanol production (36.50 g/L). Thus the loofa sponge and sugarcane bagasse represented the most promising support ...

A bactéria Zymomonas mobilis é considerada um microrganismo com alto potencial biotecnológico para a produção de etanol e levana, por apresentar baixa produção de biomassa e alta tolerância a elevadas concentrações de etanol. Apesar disso, sua eficiência pode ser prejudicada, devido a exposição das células livres a condições desfavoráveis durante os processos fermentativos convencionais. A utilização de células imobilizadas é uma alternativa para solucionar tais problemas, pois oferece inúmeras vantagens como maior concentração celular, maior estabilidade e conseqüentemente maior produção. Diante disso, o objetivo deste trabalho, foi selecionar um suporte adequado para a imobilização de Zymomonas mobilis visando aumentar a produção de etanol e levana empregando sacarose como fonte de carbono. Os suportes avaliados foram: alginato, quitosana, bucha vegetal e bagaço de cana. Os melhores parâmetros para a produção de etanol e levana, foram determinados utilizando a metodologia de superfície de resposta (MSR). O primeiro experimento realizado foi 2(5-2) com as variáveis independentes: concentração de sacarose; pH; tempo de incubação; temperatura e agitação do meio de cultura. Com base nas melhores condições observadas no experimento 2(5-2) foi avaliada a capacidade de reutilização dos suportes em fermentações subseqüentes durante 12 dias. A produção de etanol foi determinada pelo método de microdifusão e a levana foi determinada indiretamente em unidades de frutose após hidrólise ácida. A biomassa foi determinada por densidade ótica a 570 nm e a fixação do microrganismo no suporte foi confirmada por microscopia eletrônica de varredura. No experimento 2(5-2), verificou-se que o melhor suporte de imobilização foi a bucha vegetal, a qual apresentou os maiores valores de biomassa imobilizada (2,95 g/L); produção de levana (24,9 g/L) e etanol (50,95 g/L). Para os experimentos com ...
Keywords: Biotecnologia; Álcool - Indústria; Zymomonas mobilis; Celulas imobilizadas; Frutanos; Biotecnologia